Living life precariously with rheumatoid arthritis - a mega-ethnography of nine qualitative evidence syntheses - Toye, F; Seers, K; Barker, K (BioMed Central, 2019)
Background: Rheumatoid arthritis is an autoimmune disease that causes joint inflammation. It affects around 400,000 people in the UK and 1 million adults in the USA. Given the appropriate treatment, many can have relatively few symptoms. It is therefore important to understand what it is like to live with rheumatoid arthritis and gain insight into peoples' decisions about utilising healthcare. The aims of this study were: (1) to bring together qualitative evidence syntheses that explore patients' experience of living with rheumatoid arthritis and (2) develop a conceptual understanding of what it is like to live with rheumatoid arthritis. Methods: We used the methods of mega-ethnography. The innovation of mega-ethnography is to use conceptual findings from qualitative evidence syntheses as primary data. We searched four bibliographic databases from inception until September 2018 to identify qualitative evidence syntheses that explored patients' experience of rheumatoid arthritis. Results: We identified 373 qualitative evidence syntheses, removed 179 duplicates and screened 194 full text studies. We identified 42 qualitative evidence syntheses that explored the experience of pain or arthritis and 9 of these explored the experience of rheumatoid arthritis. We abstracted ideas into 10 conceptual categories: (1) rheumatoid arthritis is in control of my body (2) rheumatoid arthritis alters reciprocity; (3) rheumatoid arthritis is an emotional challenge; (4) rheumatoid arthritis disrupts my present and future self; (5) the challenge of balancing personal and work life; (6) I am trying to make sense of what is happening; (7) rheumatoid arthritis is variable and unpredictable; (8) rheumatoid arthritis is invisible; (9) I need a positive experience of healthcare, and (10) I need to reframe the situation. We developed a conceptual model underpinned by living life precariously with rheumatoid arthritis. Conclusions: This is the second mega-ethnography, or synthesis of qualitative evidence syntheses using the methods of meta-ethnography. Future research should consider the proliferation of qualitative evidence synthesis in order to avoid duplication of research effort. Our model for rheumatoid arthritis has some important clinical implications that might be transferable to other musculoskeletal conditions.